Pengaruh Modifikasi Latihan pada Teknik Tendangan Sabit pada Atlet Pencak Silat - Sri Rezeki Amelia; Raffly Henjilito (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2024)
This study investigated the impact of modified sickle kick training on the performance of pencak silat athletes. The sickle kick, an important technique in pencak silat, requires an optimal blend of speed, precision, and power. This study proposed exercise modifications involving variations in intensity, frequency, and complexity of movements, hypothesising that these changes would increase the effectiveness of the exercises. Using a pre-test and post-test experimental design, the study involved 40 pencak silat athletes (20 male, 20 female, ages 18-25) who were randomly assigned to experimental and control groups. The experimental group participated in a modified training regimen for 8 weeks, while the control group engaged in conventional training. Measurements assessed included kick execution speed, accuracy, and strength. The analysis results revealed significant improvements in the experimental group relative to the control group. Kick execution speed improved by 15% (p < 0.01), target accuracy by 25% (p < 0.001), and kick strength by 20% (p < 0.001) in the experimental group. In contrast, the control group showed only small improvements in all measures (5-8%, P > 0.05 for speed, p < 0.05 for accuracy and strength). These results suggest that modifying the sickle kick exercise is an effective strategy to improve the performance of pencak silat athletes. The implications of this study may revolutionise pencak silat training methodology and inspire similar adaptations in other martial arts disciplines.